The manor house : [large type] a novel - Macmillan, Gilly (Harper Large Print, an imprint of HarperCollinsPublishers, 2023)
Childhood sweethearts Nicole and Tom are a normal, loving couple--until a massive lottery win changes their lives overnight. Soon they've moved into a custom-built state-of-the-art Glass Barn on the stunning grounds of Lancaut Manor in Gloucestershire. They have fancy cars, expensive hobbies, and an exclusive lifestyle they never could have imagined. But this dream world quickly turns into a nightmare when Tom is found dead in the swimming pool. Nicole is devastated. Tom was her rock. And their beautiful barn --with all its smart features that never seem to work for her--is beginning to feel very lonely. But she's not entirely by herself out there in the country. There's a nice young couple who live in the Manor itself along with their middle-aged housekeeper who has the Coach House. And an old friend of Tom's from school has turned up to help her get through her grief. But big money can bring big problems and big threats. Was Tom's death a tragic accident, or was it something worse? And is her life in danger as well? Nicole's beginning to feel like a little fish in a big glass bowl. Surrounded by piranhas.